Central and East European labor markets in transition: Developments, causes, and cures - Wolfgang Franz (Universität Konstanz, Forschungsschwerpunkt Internationale Arbeitsmarktforschung, 1994)
The main questions addressed in this paper are, firstly, how labor markets in the Visegard countries reacted to the breakdown of a command economy and the transformation to a market economy. Secondly, it is analyzed which way ahead is likely, or to put it differently, what should be done now to improve conditions in the labor market in these countries. A comprehensive survey of labor market developments in each country under consideration is offered at some length. A special emphasis is then put on the dynamics of employment and unemployment in order to identify key issues for the sources of the malfunctioning of these labor markets. Issues dealt with are then the wage formation process including institutional settings and income policies, active and passive labor market policies, and the structure of employment and output.
Keywords: 330; Arbeitsmarkt; Systemtransformation; Lohnpolitik; Arbeitsmarktpolitik; Ostmitteleuropa